Photogalvanic effect in monolayer transition metal dichalcogenides under double illumination. (24th May 2019) - Entin, M V; Magarill, L I; Kovalev, V M
Abstract: We study the photogalvanic effect caused by a simultaneous action of two light sources: circular-polarized interband and linearly-polarized intraband. It is found that, in such conditions, the steady photocurrent appears. The effect originates from the valley-selective pumping by the circular-polarized light, the trigonal symmetry of the valleys and the linear polarization of intraband electromagnetic field, that produces a polar in-plane asymmetry of the electron and hole distribution functions, leading to the photocurrent. The approach is based on the solution of the classical kinetic equation for carriers with accounting for the quantum interband excitation.